Optimal Hydrophobicity and Reorientation of Amphiphilic Peptides Translocating through Membrane - Kabelka, Ivo; Vácha, Robert (Biophysical journal, 2018)
Cell-penetrating and some antimicrobial peptides can translocate across lipid bilayers without disrupting the membrane structure. However, the molecular properties required for efficient translocation are not fully understood. We employed the Metropolis Monte Carlo method together with coarse-grained models to systematically investigate free-energy landscapes associated with the translocation of secondary amphiphilic peptides. We studied α-helical peptides with different length, amphiphilicity, and distribution of hydrophobic content and found a common translocation path consisting of adsorption, tilting, and insertion. In the adsorbed state, the peptides are parallel to the membrane plane, whereas, in the inserted state, the peptides are perpendicular to the membrane. Our simulations demonstrate that, for all tested peptides, there is an optimal ratio of hydrophilic/hydrophobic content at which the peptides cross the membrane the easiest. Moreover, we show that the hydrophobicity of peptide termini has an important effect on the translocation barrier. These results provide general guidance to optimize peptides for use as carriers of molecular cargos or as therapeutics themselves.
Keywords: Hydrophobic and Hydrophilic Interactions; Peptides; Thermodynamics; peptidy; Protein Transport; termodynamika; Cell Membrane; Molecular Dynamics Simulation; Protein Conformation; simulace molekulární dynamiky; buněčná membrána; Monte Carlo Method; konformace proteinů; transport proteinů; hydrofobní a hydrofilní interakce; metoda Monte Carlo